The Influence of Customer Experience, Product Bundling, and Product Variety on the Interest in Buying Back Coffee Memories in Bandar Lampung in the Perspective of Islamic Business - Elta Metia; Adib Fachri; Agus Kurniawan (Universitas KH. Abdul Chalim Mojokerto, 2025)
The increasing competition in Indonesia’s coffee beverage industry requires businesses to maintain customer loyalty, including Kopi Kenangan Ruko Ahmad Yani Branch in Bandar Lampung, which experienced a sales decline in 2021–2022. This study aims to analyze the influence of customer experience, product bundling, and product variety on consumers’ repurchase intention from an Islamic business perspective. A quantitative approach was used with purposive sampling involving 200 respondents who had made at least two purchases. Data were collected using a five-point Likert scale questionnaire and analyzed using SmartPLS 4 to test validity, reliability, and the relationships between variables. The results indicate that all independent variables positively and significantly affect repurchase intention, implying that customer experience, bundling offers, and product variations play an important role in shaping customer loyalty. This study provides strategic implications for implementing marketing practices aligned with Islamic principles, such as honesty, product halalness, and fair service, to support business sustainability in an increasingly competitive market environment.